Characterization of the miiuy croaker (Miichthys miiuy) transcriptome and development of immune-relevant genes and molecular markers. - Rongbo Che; Yueyan Sun; Dianqiao Sun; Tianjun Xu (PLoS ONE)
Background The miiuy croaker (Miichthys miiuy) is an important species of marine fish that supports capture fisheries and aquaculture. At present commercial scale aquaculture of this species is limited due to diseases caused by pathogens and parasites which restrict production and limit commercial value. The lack of transcriptomic and genomic information for the miiuy croaker limits the ability of researchers to study the pathogenesis and immune system of this species. In this study we constructed a cDNA library from liver, spleen and kidney which was sequenced using Illumina paired-end sequencing to enable gene discovery and molecular marker development. Principal findings In our study, a total of 69,071 unigenes with an average length of 572 bp were obtained. Of these, 45,676 (66.13%) were successfully annotated in public databases. The unigenes were also annotated with Gene Ontology, Clusters of Orthologous Groups and KEGG pathways. Additionally, 498 immune-relevant genes were identified and classified. Furthermore, 14,885 putative simple sequence repeats (cSSRs) and 8,510 putative single nucleotide polymorphisms (SNPs) were identified from the 69,071 unigenes. Conclusion The miiuy croaker (Miichthys miiuy) transcriptome data provides a large resource to identify new genes involved in many processes including those involved in the response to pathogens and diseases. Furthermore, the thousands of potential cSSR and SNP markers found in this study are important resources with respect to future development of molecular marker assisted breeding programs for the miiuy croaker.